2009
DOI: 10.1007/s11684-009-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction and identification of lentiviral RNA interference vector of rat leptin receptor gene

Abstract: Leptin resistance is a main mechanism of acquired childhood obesity, and the suppression of long form of leptin receptor (OBRb) gene expression in dietinduced obese rats indicates that the down-regulation of OBRb gene expression plays a pivotal role in the mechanism of leptin resistance. The aim of the present study was to construct the lentiviral RNA interference (RNAi) vector of rat OBRb gene and evaluate the effects of siRNA on silencing OBRb gene expression. The target sequence of siRNA-OBRb was designed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The Lrb-shRNA recombinant plasmids were transfected into the rat C6 glioma cells (American Type Culture Collection, Manassas, VA, USA) to determine the inhibiting efficiency by immunofluorescence microscopy and a real-time RT-PCR. The RNAi protocol specifically reduced the expression of Lrb mRNA by w80% in transfected rat glioma cells (Liu et al 2009). …”
Section: Design and Construction Of Shrnamentioning
confidence: 99%
“…The Lrb-shRNA recombinant plasmids were transfected into the rat C6 glioma cells (American Type Culture Collection, Manassas, VA, USA) to determine the inhibiting efficiency by immunofluorescence microscopy and a real-time RT-PCR. The RNAi protocol specifically reduced the expression of Lrb mRNA by w80% in transfected rat glioma cells (Liu et al 2009). …”
Section: Design and Construction Of Shrnamentioning
confidence: 99%
“…Chaos studies have been observed in many branches of science, such as biology, medicine, ecology, electronics, economics, encryption, etc. (Wang et al 2016;Liu et al 2009;Sun et al 2020;Pandey et al 2016;Rajagopal et al 2019). Bibliometric analysis is a common technique for researching and analyzing vast scientific data.…”
Section: Introductionmentioning
confidence: 99%